Micromorphology, physicochemical parameters, and phytochemical screening of Chloranthus flavus D.T. Liu & G. Chen (syn. C. nervosus Collett & Hemsl.) from Vietnam - TRAN VAN CHEN; DUONG NGUYEN XUAN LAM; HOANG DAC KHAI; DUONG PHAN NGUYEN DUC; NGUYEN THI NGA; NGUYEN THI THU HIEN; TRAN THI THUY QUYNH (Society for Indonesian Biodiversity, 2024)
Abstract. Chen TV, Lam DNX, Khai HD, Duc DPN, Nga NT, Hien NTT, Quynh TTT. 2024. Micromorphology, physicochemical parameters, and phytochemical screening of Chloranthus flavus D.T. Liu & G. Chen (syn. C. nervosus Collett & Hemsl.) from Vietnam. Biodiversitas 25: 846-858. Chloranthus flavus D.T. Liu & G. Chen (syn. C. nervosus Collett & Hemsl.) is a subshrub belonging to the family Chloranthaceae. Information on the anatomical structure and the powder features of C. flavus has not been noted. This study aimed to develop a monograph on the microscopic characteristics and physicochemical parameters of C. flavus, as well as a preliminary assessment of the phytochemical composition of this species. Anatomical characterizations of roots, stems, and leaves were performed using the iodine green-carmine staining method and then an optical microscope was used to observe the histology of these parts, similar to observing powder characteristics. Secondary metabolites were detected by chromogenic or precipitation reagents. Anatomically, the structural characteristics of the roots, stems, and leaves are similar to those of the Chloranthus species. Particularly, the root structure is characterized by six alternating xylem bundles, with six phloem bundles forming a ring. Polygonal to irregularly shaped cells of the upper epidermis and irregularly shaped ordinary cells, laterocytic and anomocytic stomata types, stomatal clusters, and the stomatal index (15.75±1.52%) of the lower epidermis were observed in leaves. Both powders found fragments of epidermal and parenchymatous cells, spiral xylem vessels, and scalariform xylem vessels. However, the root powder only observed solid-shaped sclereid cells, starch granules, starch clusters, and calcium oxalate crystals. The powders' moisture content, total ash, and acid-insoluble ash values all meet acceptable standards according to regulations on raw material purity. The whole C. flavus plant contains carotenoids, fatty acids, essential oils, flavonoids, tannins, coumarins, alkaloids, triterpenoids, amino acids, and carbohydrates. The current findings highlight the key characteristics for identifying C. flavus.